Roles of Impulsivity, Motivation, and Emotion Regulation in Procrastination – Path Analysis and Comparison Between Students and Non-students - Wypych, Marek; Matuszewski, Jacek; Dragan, Wojciech Ł. (Frontiers in Psychology, 2018)
Procrastination – an irrational delay of intended actions despite expecting to be worse off – is a complex and non-homogenous phenomenon. Previous studies have found a number of correlates of procrastination, some of which seem to be particularly important. Impulsivity is closely connected to procrastination on behavioral, genetic, and neuronal levels. Difficulties in emotion regulation have also been shown to be strongly related to procrastination. Procrastination can also be considered as a motivation-based problem. To try to disentangle the connections of impulsivity, emotion regulation, and motivation to procrastination we collected data from over 600 subjects using multiple questionnaires (PPS – Pure Procrastination Scale; UPPSP – Impulsive Behavior Scale, ERQ – Emotion Regulation Questionnaire and MDT – Motivational Diagnostic Test). Structural equation modelling was performed to test several possible relationships between the measured variables. The effects of student status and age have also been investigated. The final path model was a directional model based on six explanatory variables and accounted for 70% of the variance in procrastination. Path analysis revealed that the strongest contributions to procrastination came from lack of value, delay discounting, and lack of perseverance, suggesting the involvement of motivation and impulsivity. The model also revealed the moderating role of expressive suppression between several aspects of impulsivity and procrastination. Close inspection of the paths’ weights suggests that there may be two partly competing strategies for dealing with impulsivity and negative emotions: either to suppress emotions and impulsive reactions or to react impulsively, discarding previous plans, and to procrastinate. Path invariance analysis showed the significant moderating roles of student status and age. Both in non-students and high-age groups, the path leading from suppression to procrastination was insignificant. This suggests that caution should be used in generalizing the results of studies carried out on students. These results support previous findings that procrastination may serve as a short-term mood regulation strategy. However, as the spectrum of the emotion regulation strategies included in the study was very limited, we conclude that future studies should seek more insight into the relationship between emotion regulation, self-control, and procrastination.